The Race between Demand and Supply: Tinbergen's Pioneering Studies of Earnings Inequality - James J. Heckman (Institute of Labor Economics (IZA), 2018)
Understanding inequality and devising policies to alleviate it was a central focus of Jan Tinbergen's lifetime research. He was far ahead of his time in many aspects of his work. This essay places his work in the perspective of research on inequality in his time and now, focusing on his studies on the pricing of skills and the evolution of skill prices. In his most fundamental contribution, Tinbergen developed the modern framework for hedonic models as part of his agenda for integrating demand and supply for skills to study determination of earnings and its distribution and the design of effective policy. His lifetime emphasis on social planning caused some economists to ignore his fundamental work.
Keywords: B31; D31; D33; D63; I24; J20; P21; 330; income inequality; hedonic models; general equilibrium; models of inequality